Sistem Informasi Pencarian Rute Terpendek Pariwisata di Kabupaten Ende Nusa Tenggara Timur Menggunakan Algoritma Dijkstra - Ufiah, Fitriah Indrianingsih; Bata, Emanuel Safirman (Universitas Boyolali, 2024)
The Ende Regency on Flores Island, East Nusa Tenggara Province, offers various attractive tourist destinations with its natural charm and cultural richness. However, visitors to the Ende Regency face the challenge of insufficient information regarding the shortest and most efficient routes to their desired tourist spots. To address this issue, a tourism route search information system is developed for the Ende Regency using the Dijkstra algorithm-based website. The Dijkstra algorithm is employed to find the shortest route between two points in a weighted graph.Utilizing a website as the platform for this system enables easy and flexible access through various devices such as laptops, computers, and smartphones, facilitating users in utilizing the system anytime and anywhere. It is anticipated that this system will assist tourists in navigating to tourist destinations in the Ende Regency more easily and efficiently.